Deep strata geologic structure and tight sandy conglomerate gas exploration in Songliao Basin, East China - Zehui ZHAO; Shujuan XU; Xiaohua JIANG; Changsong LIN; Honggang CHENG; Junfeng CUI; Li JIA (Petroleum Exploration and Development, 2016)
Abstract: The geologic structure of deep formations, basic geologic pattern of fault depressions, geologic conditions of Lower Cretaceous Shahezi Formation tight gas reservoir, and the exploration direction in the next step in the Songliao Basin are examined based on a comprehensive and comparative analysis of the outcrop, drilling, seismic and geochemical data. Systematic comparison analysis shows that the geologic structure of deep formations in the basin is characterized by a double-layer structure with fault depression in the lower layer and depression in the upper layer. In the deep fault depression (DFD) stage, fault depressions bounded by faults or onlaps and uplifts, developed independently. The faults related to the formation and evolution of the fault depressions can be divided into regional discordogenic fault, basement depression controlling fault, and secondary fault inside depression, and their actions in the evolution of the fault depression groups are presented in the paper. Based on analysis of regional tectonics and basin evolution features, three exploration fields, tight conglomerate gas, volcanic rocks and basement buried hills are pointed out, and it is concluded the tight conglomerate gas in the Shahezi Formation is currently a new strategic field with the most promising exploration prospect. Based on comprehensive analysis of basic oil geologic features of Shahezi Formation, it is proposed that conglomerate is the main category of clastic reservoir in Shahezi Fromation, and parent rock composition, sedimentary structure and facies, and diagenesis are the main factors affecting the distribution of conglomerate reservoirs. Furthermore, the gas reservoirs in Shahezi Formation, all source and reservoir in one, include two types, lithologic and structural types. Favorable sedimentary facies belts in the gentle slope and steep slope control the distribution of the reservoirs, formation of lithologic traps and gas reservoir scale; while secondary faults inside fault depressions control the formation of structural traps and enrichment of natural gas. Finally, seven fault depressions in Shahezi Formation with the most promising prospect of tight gas have been sorted out through comprehensive evaluation. Key words: Songliao Basin, deep geologic structure, Cretaceous, Shahezi Formation, tight conglomerate gas, exploration prospect